Expression of MMR in 515 cases of endometrioid adenocarcinoma and its correlation with clinicopathological features - WU Quan, GUO Jingwei, LEI Yuxin, HU Xiaoru, WANG Zhe (Zhongguo aizheng zazhi, 2022)
Background and purpose: Lynch syndrome associated endometrial carcinoma has unique clinicopathological features and treatment methods. The detection of mismatch repair (MMR) protein expression by immunohistochemical (IHC) staining in patients with newly diagnosed endometrial cancer can effectively screen patients with Lynch syndrome associated cancer. This study investigated the expression of mismatch repair proteins (MLH1, MSH2, MSH6 and PMS2) in endometrioid adenocarcinoma and its relationship with clinicopathological features. Methods: A total of 515 cases of endometrioid adenocarcinoma were collected from Shengjing Hospital of China Medical University from January 2018 to August 2020.The patients were 28 to 81 (57.73 ± 8.41) years old. IHC method was used to detect the protein expressions of MLH1, MSH2, MSH6 and PMS2 in cancer tissues. Polymerase chain reaction (PCR) was used to detect the gene methylation of MLH1 protein expression deficient specimens, and the relationship between MMR protein expression deletion and clinicopathological features of endometrioid adenocarcinoma was analyzed. As long as there was a loss of MMR protein expression, it was judged as deficient mismatch repair (dMMR). If all MMR proteins were positive, it was judged as proficient mismatch repair (pMMR). Results: MMR protein was absent in 138 (26.8%) of 515 cases of endometrioid adenocarcinoma. The deletion rates of MLH1, PMS2, MSH2 and MSH6 proteins were 16.3% (84/515), 19.0% (98/515), 5.4% (28/515) and 8.0% (41/515), respectively. The loss of MMR protein expression was mainly the combined loss of MLH1 and PMS2 expressions (60.9%, 84/138), and the second was the combined deletion of MSH2 and MSH6 expressions (18.8%, 26/138). There were 2 cases of combined deletion of MSH2, MSH6 and PMS2 expressions (1.4%, 2/138). The single deletion rates of PMS2, MSH2 and MSH6 proteins were 8.0% (11/138), 1.4% (2/138) and 10.1% (14/138), respectively. MLH1 protein expression deletion was detected in 27 samples, and the results showed that the methylation positive rate was 85.2% (23/27). The loss of MMR protein expression in 515 cases of endometrioid adenocarcinoma was correlated with the age of onset, the International Federation of Gynecology and Obstetrics (FIGO) stage, the degree of histological differentiation, depth of invasion, vascular metastasis, nerve invasion, lymph node metastasis, abnormal expression of p53, tumor infiltrating lymphocytes and tumor with peritumoral lymphocyte infiltration. MMR protein status was not correlated with lower uterine segment involvement. Compared with pMMR patients, the onset age of dMMR was younger, and FIGO stage was mostly stage Ⅲ-Ⅳ. The histological differentiation degree was mostly low, most tumors had no myometrial infiltration, and most tumors had vascular metastasis, nerve invasion and lymph node metastasis. The lymphocyte infiltration in the tumor with dMMR was increased, and the tumor with peritumoral lymphocyte was more significant. Most patients with MSH6 protein deficiency had no abnormal expression of p53. Conclusion: Compared with pMMR patients, dMMR patients in Northeast China has unique clinicopathological characteristics. Detecting the expression of MMR protein by immunohistochemical staining and detection of the gene methylation of MLH1 expression deficient specimens can preliminarily screen patients with Lynch syndrome, which has certain guiding significance for immunotherapy of tumor patients.